An illustrated guide of subfossil Chironomidae (Insecta: Diptera) from waterbodies of Central America and the Yucatan Peninsula - Hamerlík, L. (2022)
We provide a photographic guide and taxonomic diagnosis of Chironomidae larval remains obtained from surface sediments and short cores of 92 waterbodies situated on the Yucatan Peninsula and in Central America, namely Mexico, Belize, Guatemala, El Salvador and Honduras. A total of 101 morphotypes belonging to 64 genera were identified. Chironominae was the most species-rich subfamily represented by 57 morphotypes of 34 genera. The most widespread and abundant genus was Goeldichironomus followed by Chironomus and Polypedilum. Orthocladiinae were represented by 26 morphotypes and 17 genera, with the most common one being Cricotopus. Remains of this subfamily were recorded in only 1/5 of the surveyed lakes. Tanypodinae included 17 morphotypes belonging to 12 genera. Labrundinia along with Ablabesmyia and Coelotanypus were the most common genera. Subfamily Podonominae was represented by the genus Parochlus. We believe that our study includes most of the Chironomidae genera of Central America and will have broad applicability for both paleolimnologists and aquatic ecologists.